(untitled) (Global Journal of Human-Social Science, 2024)
Racism in the United States has been a major social problem for generations Our nation s history is filled with numerous examples of multigenerational discriminatory laws and public policies that have sought to deny civil liberties to individuals of color Institutionalized inequalities in the areas of education employment housing and access to healthcare services supported by conservative lawmakers representing the broader White constituency are the catalyst that launched early social justice movements to bring about change that would create a more inclusive social order where everyone s fundamental rights are protected Although some research over the past five decades has shown broad indications that legislative changes like the ones brought about by the civil rights legislation of the 1960s have enabled some disenfranchised minority populations such as Blacks Hispanics and Asian Americans to receive civil liberties protection under the law the underlying attitudes and beliefs that support discrimination against individuals based on race have not kept pace with this progress National statistics from surveys by federal agencies provide substantial evidence that despite the enactment of new laws designed to make social political and economic systems more responsive to the rights of racial and ethnic minority groups The adverse effects of institutionalized racism continue to expand globally This chapter will critically analyze the historical socioeconomic and political factors contributing to the rise of institutionalized racism in our culture It will examine how implementing anti-discrimination laws policies and practices can create a more welcoming social order by transforming biased perceptions about race